REVISITING PRIBUMI – NONPRIBUMI DISCOURSES IN THE POST-SUHARTO INDONESIA - Raharfian, Idham (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
This study explores the ideological shifts surrounding the terms pribumi (native Indonesian) and nonpribumi (non-indigenous people) in the post-Suharto era (1998-2020). The data source are 173 news articles from the Indonesian press containing the term ‘pribumi.’ By employing Van Dijk’s ‘Ideological Square’ Critical Discourse Analysis (CDA) the study portrays groups in terms of dominance, inequality, difference, and victimization to understand power dynamics and ideological constructions in the language. The findings reveal that pribumi are portrayed positively as rooted in ethnic origin, cultural heritage, and mainly Muslim identity in recent periods, but also as economically disadvantaged landowners. Conversely, nonpribumi are depicted negatively as foreign, racially distinct, and economically dominant. Negative representations of pribumi as oppressors and politically dominant are de-emphasized, while positive portrayals of nonpribumi as passive victims are mitigated. The study suggests that evolving nuances stem from democratic transitions and heightened identity politics tensions. Economic perceptions linked to these terms persist across periods. These insights might help scholars and policymakers understand mobilization patterns and potential identity-related conflicts, prompting further research into using dichotomous terms within specific social and cultural contexts.